The legacy of American copper smelting : industrial heritage versus environmental policy - Morin, Bode J. (Knoxville : The University of Tennessee Press, 2013)
Throughout world history, copper has been a significant metal for a vast number of cultures, from the oldest civilizations on record to the Bronze Age and Greek and Roman antiquity. Though replaced by iron as the primary metal for tools and weapons in ancient civilizations, copper found new resurgence in the nineteenth century when it was discovered to have particularly high thermal and electrical conductivity. Copper mining quickly escalated into a large-scale industry, and because of its vast reserves and innovative mining techniques, the United States seized the reins of global product.
The historic roots of copper production and smelter pollution -- The American system : a technological context -- Ducktown -- Montana -- Quincy smelter.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Copper mines and mining -- Environmental aspects -- United States; Environmental policy -- United States; Copper industry and trade -- Tennessee -- Ducktown (Polk County) -- History; Copper industry and trade -- Montana -- History; Copper industry and trade -- Michigan -- Keweenaw Peninsula -- History; Cuivre -- Mines et extraction -- Aspect de l'environnement -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; Cuivre -- Industrie -- Montana -- Histoire; Cuivre -- Industrie -- Michigan -- Keweenaw, Péninsule de -- Histoire; BUSINESS & ECONOMICS -- Industries -- General; Copper industry and trade; Copper mines and mining -- Environmental aspects; Environmental policy; Michigan -- Keweenaw Peninsula; Montana; United States; SOCIAL SCIENCE / Archaeology; History